First step
is to rewrite each fraction as Numerator and denominator :
2 1/3 = 7 / 3 ( we first multiply 2 by the denominator 3 and that is 6 then we add the numerator and that will 7 now we put this number as the new numerator while we leave the denominator as is)
1 1/2 = 3 / 2 ( same as above)
our fractions now became 7 / 3 - 3 / 2 =
Second step
We look at the two denominator if they are equal that's ok if not then we must unify them
Now if look to the denominators we can that is 6 is the least common multiplier so we must multiply the first fraction (both num. and deno.) with 2 to get 6 in denominator and multiply the second fraction with 3 to get 6 in deno:
(7x2)/(3x2) - (3x3)/(2x3)
= 14 / 6 - 9 / 6
Once we unify the denominators the answer will be as follow:
14/6 - 9/6 = (14-9) / 6 = 5/6 That is all
it's easy, isn't it? Good luck